Dealing with Austria’s dark heritage and contemporary extremism. Peter Patzak’s adaptation of Helmut Zenker’s «Kassbach» (1979) (Studia austriaca, 2022)
This essay explores one of the films which dealt with the above-mentioned topics and had its cinematic release in the period under discussion – Kassbach, an adaptation of Helmut Zenker’s novel, which was made by Peter Patzak, a prominent Austrian director who passed away in 2021. In this respect, Kassbach would be a work that preceded numerous other Austrian films with a cinematic release in the 1980s and which, even before the Waldheim affair, would touch upon Austria’s difficult past. This article focuses on the film’s message that the lack of de-Nazification at the time, understood not only as a political and bureaucratic, but also as a psychological and social process, facilitates the establishment of right-wing radicalism.